2002
DOI: 10.1207/s15327914nc441_3
|View full text |Cite
|
Sign up to set email alerts
|

Diet in Relation to Endometrial Cancer Risk: A Case-Control Study in Greece

Abstract: The risk of endometrial cancer is positively associated with obesity, but the role of specific nutrients remains unclear. Given the distinct characteristics of the Greek diet and the low incidence of this form of cancer among Greek women, we undertook a case-control study to investigate the association of endometrial cancer with food groups and micronutrients. Cases were 84 women with histologically confirmed endometrial cancer and controls were 84 women with intact uterus admitted to the same teaching hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 33 publications
2
71
0
1
Order By: Relevance
“…An ecological study showed that prostate cancer mortality was inversely associated with nuts and oilseed consumption [27]. Moreover, findings from prospective studies suggest inverse associations between nut consumption and colorectal or endometrial cancer, especially in women [28]–[31]. Some studies showed inverse associations of nut intake and prostate cancer [32], however the relationship between nuts and cancer incidence and mortality is insufficient and further research is needed [33].…”
Section: Discussionmentioning
confidence: 99%
“…An ecological study showed that prostate cancer mortality was inversely associated with nuts and oilseed consumption [27]. Moreover, findings from prospective studies suggest inverse associations between nut consumption and colorectal or endometrial cancer, especially in women [28]–[31]. Some studies showed inverse associations of nut intake and prostate cancer [32], however the relationship between nuts and cancer incidence and mortality is insufficient and further research is needed [33].…”
Section: Discussionmentioning
confidence: 99%
“…More recent reports support a preventive role, although limited to women [56,57,58,59]. A small case-control study in Greek women [60] suggests that a diet rich in nuts, seeds and pulses reduces the risk of endometrial cancer by 27% compared to infrequent consumption of such foods. Results from the large EPIC study [61] showed no relation between higher intake of nuts and seeds and risk of colorectal cancers in the whole cohort or in men alone, but an inverse association was detected in women between the highest quintile of nut consumption (>6.2 g/day) and the lowest quintile (non‑consumers), with an adjusted odds ratio of 0.69 (CI, 0.50 to 0.95).…”
Section: Epidemiological Studies Of Nut Consumption and Health Outmentioning
confidence: 99%
“…In addition to one animal study [10] and four ecologic studies [11][12][13][14], three manuscripts were excluded for presenting data for foods or food groups only [15][16][17]. Three additional manuscripts were excluded for not presenting risk estimates [9,18,19].…”
Section: Manuscript Selection and Data Extractionmentioning
confidence: 99%